Finite element computation of turbulent compressible flows based on the k- E model and SUPG stabilization - Mohammadi, Bijan (European Journal of Computational Mechanics, 1993)
The conservative Navier-Stokes and the k - E equations are solved using a stabilized Streamline Petrov-Galerkin technique. The stabilization techniques employed are described and several numerical examples are reported. Comparison with analytical or experimental data for these cases shows that this technique may be a good alternative for computing complexe configurations of turbulent compressible flows. Specially this approach seems to be interesting because the simplicity of its formulation and also a possible easy extension to three dimensional configurations.